Penerapan data mining dalam analisa profil mahasiswa menggunakan metode support vector machines (SVM) - Luki Hernando; Vitri Aprilla Handayani; Deosa Putra Caniago; Nadia Widari Nasution (Universitas Muhammadiyah Riau, 2023)
decision making. The Support Vector Machine algorithm is a method in supervised learning which is usually used for classifications such as Support Vector Classification and support Vector Regression regression. In this study the SVM algorithm was used in the classification of student data profiles at the Batam Institute of Technology, which can be used as material for consideration in determining and considering decisions to make an effective destination strategy promotion.